Effect of Zn Nanoparticles Doping on Oxytetracycline Removal by Natural Aluminosilicate and Carbon Nanotubes - Morales- Serrato, Denisse Alejandra; Torres Perez, Jonatan; Reyes-López, Simón Yobanny; Ruíz-Baltazar, Álvaro de Jesús (2022)
The presence of antibiotics such as oxytetracycline (OTC) in water and wastewater is considered an environmental problem and, consequently, their elimination is an important topic. The present research shows the removal of OTC from aqueous medium using a quartz-based natural aluminosilicate (Q) and carbon nanotubes (CNTs) modified with zinc nanoparticles (ZnNPs) as alternative adsorbent materials for OTC removal. The ZnNPs were synthesized by chemical reduction method and were used to modify the Q and CNT surface. There were obtained four materials (Q, Q/ZnNPs CNTs. and CNTs/ZnNPs) characterized by SEM–EDX, FTIR, DRX, and pHPZC. The adsorption behavior of OTC, as a function of drug concentration, pH, and temperature, was investigated by adsorption experiments. High adsorption capacities (qe) of OTC as 644 and 111 mg/g were obtained for CNTs and CNTs/ZnNPs, respectively. For Q and Q/ZnNPs, the maximum OTC sorption was 177 and 78 mg/g, respectively. It was found that OTC adsorption process using CNTs and CNTs/ZnNPs follows a pseudo-second-order and intraparticle diffusion, while when using the Q and Q/Zn, it follows a pseudo-first-order model. Moreover, isotherm tests were performed on distilled water and drinking water to evaluate the effect of ionic strength. The obtained data were adjusted to Langmuir, Freundlich, Temkin, and Dubinin-Raduskevich isotherm equations, being Freundlich the isotherm that describes the OTC sorption process. The results obtained were indicative of a good OTC adsorption capacity by the alternative prepared materials.